System for creation, programming and availability of distributed robot teams using collective knowledge - Silva, Paulo Henrique Lopes (2018)
This paper addresses the problem of programming, control and availability of distributed robots teams. Systems based on robots working together collaboratively has been the subject of much research in recent years. For distributed robots systems there is a latent need for research to enable the use of such systems by end users with no or almost no experience with programming or robotics. Thus, this paper proposes a system architecture that allows the creation and programming of robot teams, allowing and users to manage them as a single system and simple way using collective knowledge acquired both programmers as of the and users. The tests are performed by an application that was developed under the concepts of this architecture. It provides a set of special operations by which and users can connect, create and control robots teams at high level. The process of creation, programming and control of two teams is presented in well defined steps. The results are satisfactory and show that the operating strategy of the proposed system meets fundamental aspects at the system level such as modularity, flexibility and ease of access for end users